BIOCHEMICAL MARKERS AND BONE HEALING OUTCOMES IN POST-COVID-19 LONG BONE FRACTURE PATIENTS - Badriddinov Akobir Sadriddinovich,; Khamdamov Bakhtiyor Zaripovich, (Ta'limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2025)
Annotation Bone healing may be significantly compromised in patients recovering from COVID-19 due to metabolic disturbances. Vitamin D deficiency and inflammatory imbalance are key contributing factors. Identifying biochemical predictors is crucial for targeted treatment. This article provides scientific research information about biochemical markers and bone healing outcomes in post-COVID-19 long bone fracture patients.